Molecular control of masting: an introduction to an epigenetic summer memory. (21st January 2020) - Samarth,; Kelly, Dave; Turnbull, Matthew H; Jameson, Paula E
Abstract: Background: Mast flowering ('masting') is characterized by mass synchronized flowering at irregular intervals in populations of perennial plants over a wide geographical area, resulting in irregular high seed production. While masting is a global phenomenon, it is particularly prevalent in the alpine flora of New Zealand. Increases in global temperature may alter the masting pattern, affecting wider communities with a potential impact on plant–pollinator interactions, seed set and food availability for seed-consuming species. Scope: This review summarizes an ecological temperature model (Δ T ) that is being used to predict the intensity of a masting season. We introduce current molecular studies on flowering and the concept of an 'epigenetic summer memory' as a driver of mast flowering. We propose a hypothetical model based on temperature-associated epigenetic modifications of the floral integrator genes FLOWERING LOCUS T, FLOWERING LOCUS C and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 . Conclusions: Genome-wide transcriptomic and targeted gene expression analyses are needed to establish the developmental and physiological processes associated with masting. Such analyses may identify changes in gene expression that can be used to predict the intensity of a forthcoming masting season, as well as to determine the extent to which climate change will influence the mass synchronized flowering of masting species, with downstream impacts on their associated communities.